An observational study of extracorporeal CPR for in-hospital cardiac arrest secondary to myocardial infarction. Issue 6 (9th October 2013) - Chou, Tzung-Hsin; Fang, Cheng-Chung; Yen, Zui-Shen; Lee, Chien-Chang; Chen, Yih-Sharng; Ko, Wen-Je; Wang, Chih-Hsien; Wang, Sheoi-Shen; Chen, Shyr-Chyr
Abstract : Objective: To determine the effects of extracorporeal cardiopulmonary resuscitation (ECPR) in patients with in-hospital cardiac arrest (IHCA) due to acute myocardial infarction (AMI). Methods: IHCA patients due to AMI undergoing CPR between 1 January 2006 and 1 July 2010 were analysed retrospectively. We compared the survival outcome of 43 patients who received ECPR with that of 23 patients who underwent conventional CPR. Results: The survival rate was 34.9% for patients who received ECPR and 21.8% for those who received conventional CPR (p=0.4). Increased survival rates to hospital discharge were seen in patients with ST segment elevation (p<0.01), or had initial rhythm of ventricular tachycardia/ventricular fibrillation (VT/VF) during resuscitation (p=0.031). Conclusions: ECPR may improve survival in cardiac arrest patients who have a ST segment elevation or initial rhythm of VT/VF myocardial infarction.